Implementation of the Routine Habituation Method in Developing Reading Skills in Elementary Schools - Nopianto, Muhamad; Sukarto, Sukarto; Marzoan, Lalu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is based on reading habits that occur as a result of routine activities carried out daily at school. The aim of this research is to describe the implementation of the habituation method applied by class IV students at SDN 4 Gondang. This research was carried out at SDN 4 Gondang, Gangga District in class IV semester II of the 2023/2024 academic year. The method used in this research is a qualitative approach and in terms of method it is a descriptive method. Data collection techniques use observation, interviews and documentation techniques. The data sources for this research are school principals, teachers and students. And the data analysis techniques used in this research are data collection, data reduction, presentation and drawing conclusions. The research results show that (1) Implementation of the reading habitual method in an effort to foster reading skills at SDN 4 Gondang is carried out by a) reading habitually, b) providing a reading corner c) and providing reading books in the library and each class. (2) There are obstacles and solutions to implementing the habituation method (1) internal factors (a) reading disorders, the solution is with special guidance to students, (b) lack of focus on reading, the solution is to stay away from places that can interfere with the reading process or by reporting to teachers, (2) External factors, (a) lack of reading facilities, the solution is to utilize unused facilities and use them to facilitate the lack of reading places, (b) lack of reading time, the solution is to provide reading time when there is time blank.